Relax, the expansion of the universe is still accelerating - Davis, Tamara (New Zealand Science Review, 2016)
​ There’s been a whirlwind of commentary of late, speculating that the acceleration of the expanding universe might not be real after all. It follows the publication this month of a new look at supernovae in our universe, which the researchers say give only a ‘marginal detection’ of the acceleration of the universe. This seems to be a big deal, because the 2011 Nobel Prize in Physics was awarded to the leaders of two teams that used supernovae to discover that the expansion of the universe is speeding up. But never have I seen such a storm in a teacup. The new analysis, published in Scientific Reports, barely changes the original result, but puts a different (and in my opinion misleading) spin on it. So why does this new paper claim that the detection of acceleration is ‘marginal’? Well, it is marginal if you only use a single data set. After all, most big discoveries are initially marginal. If they were more obvious, they would have been discovered sooner.